Ruxolitinib is effective in the treatment of a patient with refractory T-ALL - Jaramillo Segura, Sonia; Hennemann, Hannah Mai; Horak, Peter; Teleanu, Maria-Veronica; Heilig, Christoph E.; Hutter, Barbara; Stenzinger, Albrecht; Glimm, Hanno; Goeppert, Benjamin; Müller-Tidow, Carsten; Fröhling, Stefan; Schönland, Stefan; et al. (eJHaem, 2021)
T-cell acute lymphoblastic leukemia (T-ALL) is a rare, aggressive T-cell malignancy. Chemotherapy alone cures only 25-45% of the cases, thus, novel treatment agents and strategies are urgently needed. We assessed the efficacy of ruxolitinib in a patient with a cutaneous relapse after allogeneic blood cell transplantation of a refractory T-ALL with a Janus kinase 3 (JAK3) mutation. In this case report, we were able to show the potential benefit of the JAK inhibitor ruxolitinib in JAK3-mutated refractory T-ALL and emphasize the importance of integrating molecular markers in current treatment decision making for patients with T-ALL.